Differing Climatic Mass Balance Evolution Across Svalbard Glacier Regions Over 1900–2010 - Möller, Marco; Kohler, Jack (Frontiers in Earth Science, 2018)
Relatively little is known about the glacier mass balance of Svalbard in the first half of the 20th century. Here, we present the first century-long climatic mass balance time series for the Svalbard archipelago. We use a parameterized mass balance model forced by statistically downscaled ERA-20C data to model climatic mass balance for all glacierized areas on Svalbard with a 250 m resolution for the period 1900–2010. Results are presented for the archipelago as a whole and separately for nine different subregions. We analyze the extent to which climatic mass balance in the different subregions mirror the temporal evolution of the climate warming signal, especially during the early 20th century Arctic warming episode. The spatially averaged mean annual climatic mass balance for all Svalbard is balanced at –0.002 m w.e. with an associated mean equilibrium line altitude of 425 m a.s.l.. When also taking calving fluxes into account, this status leads to an archipelago-wide cumulative mass balance of 16.9 m w.e. over the study period, equaling a sea level equivalent of 1.6 mm. The long-term evolution of climatic mass balance is largely governed by ablation variability. Refreezing contributes 34% to the archipelago-wide mass gain on average. Considerable variability is evident across Svalbard, with predominantly positive climatic mass balances in the northeastern parts of the archipelago and mostly negative ones in the western and southern parts. The archipelago-wide climatic mass balance shows a statistically significant trend of 0.021 m w.e. per decade and the associated equilibrium line altitude rises with a likewise significant trend of +3.0 m a.s.l. per decade. Spatial variability of the equilibrium line is such that the lowest altitudes are reached across the eastern islands of the archipelago and the highest ones in the central parts of Spitsbergen.